Self Efficacy And The Quality Of Life Of Schizophrenia Caregivers - Mulyanti Ners; Brune Indah Yulitasari (Alma Ata University Press, 2019)
Self efficacy is an important factor to improve the quality of life of Schizophrenia caregivers. A caregiver’s quality of life affects treatment process which is an important key in curing Schizophrenia patient. This research aims to investigate the relation of self-efficacy to the quality of life. This is a quantitative research with cross sectional approach. The research was conducted in the working area of Puskesmas Godean I, i.e. Desa Sidoluhur, Desa Sidoagung, Desa Sidomulyo, and Desa Sidomoyo on August 1 to September 15, 2018. There were 47 participants chosen using consecutive sampling technique. The dependent variable is the quality of life of Schizophrenia caregivers. Meanwhile, the independent variable is self-efficacy. Both variables were measured through questionnaire. The quantitative data was analyzed using chi square test. The characteristics of the research subjects are: female, middle aged, married, low-income earners, senior high school graduates, and have caring experience of more than 5 years. It is found that the self-efficacy of schizophrenia caregivers is in ‘strong’ category. There is a significant relation between the self-efficacy of Schizophrenia caregivers and their quality of life. The quality of life of Schizophrenia caregivers is influenced by high level of self-efficacy.